Interaction Dynamics in a Participatory Interpretation Group: Critical Reflections on the Status of Lifeworld Knowledge in a Group Interpretation of Scientists and Adolescents - Heeg, Rahel; Steiner, Olivier; Schmid, Magdalene (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2021)
The starting point for this article was the observation that the inclusion of young researchers in groups, interpreting qualitative data led to a quick finalization of the interpretations. In this article we describe these processes. The focus is on the status of the co-researchers as experts of their lifeworld and the impact of this status on the interpretation process. Our aim is to provide insight into (for the research team unexpected) dynamics in the interpretation process. Collective interpretation processes in groups are of great importance in qualitative research in general and especially in participatory research. Following the goals and rules of "classical" interpretation in groups, to conduct interpretation sessions together with non-academic researchers seems inadequate if they are untrained. Following the goals and rules of participatory research, a quick(er) finalization of the interpretation process is justifiable since the results are based on the knowledge of lifeworld-experts. We describe the experiences in a participatory research project in which power dynamics unfolded in an unexpected way by granting the young co-researchers the final authority in the interpretation process. These experiences are critically discussed. The present findings raise further questions for interpretation groups beyond participatory research.